Odor-removing temperature-control sand-containing fog sealing layer and preparation method thereof
By spreading the asphalt pavement with odor-controlled temperature-controlled microcapsules containing composite shell and core materials and a fog sealing layer material with fine sand particles, the problems of cracking, particle drop and irritating gas release occurring during the high temperature of the sun and sun, the pavement temperature regulation and pollutant inhibition are achieved, and the pavement service life is extended.
Patent Information
- Application Number
- CN202311358792.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art cannot effectively solve the problems of cracking, particle dropping and irritating gas release during asphalt pavement under the action of high sunlight, affecting driving safety and road life.
A clean smell and temperature-controlled sand-containing mist sealing layer material is developed. By spreading the asphalt surface layer with a temperature-controlled microcapsule containing composite shell and core materials, combined with fine sand particles, road surface temperature regulation and pollutant inhibition are achieved.
Effectively inhibit pollutants released by asphalt pavement under high temperature sun exposure, reduce pavement temperature, extend the service life of asphalt pavement, and avoid discomfort on human body.
Smart Images

Figure CN119859032A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of special asphalt, and specifically relates to an odor-free temperature-controlled sand-containing fog seal layer and a preparation method thereof. Background Art
[0002] In recent years, China's transportation industry has developed rapidly, and the mileage of newly built roads has increased year by year. As of 2022, the total mileage of national roads has reached 5.35 million kilometers, basically meeting the travel needs of Chinese residents. Among the many road forms, asphalt pavement has become the main form of highway pavement at this stage due to its good noise reduction ability and excellent anti-skid performance. However, due to its dark color, asphalt pavement will have some problems during the application process due to the effect of sunlight. For example, during the service process, asphalt ages, cracks, and granules appear, affecting driving safety; macromolecular compounds in the asphalt system are cracked to form small molecules under the action of thermal oxygen, which further evaporates under heat to produce irritating gases, causing harm to the human body.
[0003] CN116285687A discloses a phase-change mist seal material containing phase-change material, and its preparation method and application. The method spreads the mist seal material containing phase-change material on the asphalt surface layer, and while repairing the road surface, reduces the road surface temperature by means of the phase-change heat absorption capacity of the phase-change material, thereby achieving the purpose of reducing the amount of smoke released from the road surface and reducing road surface diseases. However, the material provided by the patent can only passively reduce the amount of smoke released from asphalt, and the phase-change material in the material system may cause oil spillage on the road surface during the phase change process, affecting driving safety.
[0004] In summary, the existing technology cannot effectively solve a series of problems that arise when the road surface is exposed to high temperatures in the sun. Therefore, it is very necessary to develop a material that can repair existing road surface defects and effectively prevent the road surface from being damaged by high temperatures in the sun during subsequent applications. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a deodorizing temperature-controlling sand-containing fog seal and a preparation method thereof. The deodorizing temperature-controlling sand-containing fog seal material of the present invention not only has good road performance and temperature control performance, but also can effectively suppress the amount of pollutants generated by asphalt pavement under high temperature and sunlight, providing a new idea for the functional utilization of asphalt materials.
[0006] The first aspect of the present invention provides a deodorizing temperature-controlling sand-containing fog seal layer, which comprises the following components in parts by mass:
[0007] Asphalt: 35-70 parts;
[0008] Water: 30-70 parts;
[0009] Composite emulsifier: 2-8 parts;
[0010] Defoaming agent: 0.5-3 parts;
[0011] Latex: 5-40 parts;
[0012] Suspension: 20-40 parts;
[0013] Fine sand: 20-45 parts;
[0014] Odor-free temperature-control microcapsules: 5-40 portions;
[0015] The odor-free temperature-controlling microcapsule comprises a composite shell material and a core material, wherein the composite shell material comprises silicon dioxide / nano-tourmaline / polydopamine, the core material comprises normal alkanes with a phase transition temperature of 40-60°C, and the surface of the composite shell material is loaded with metal chelates and smoke-suppressing compounds containing active α-H.
[0016] Furthermore, the asphalt is commercially available No. 70 or No. 90 base asphalt.
[0017] Furthermore, the composite emulsifier includes a cationic emulsifier and an amphoteric emulsifier, and the mass ratio of the cationic emulsifier to the amphoteric emulsifier is 1:0.5-2.5.
[0018] Further, the cationic emulsifier includes one or more of amine salt type surfactants with a carbon number greater than 8; preferably one or more of tetradecyl-dimethylpyridinium ammonium bromide, octadecylamidopropyl dimethyl dihydroxypropyl ammonium chloride, behenic acid amide propyl dimethyl dihydroxypropyl ammonium chloride, hexadecylamidopropyl trimethyl ammonium chloride, dioctadecyl-methylbenzyl ammonium chloride, dodecyl dimethylbenzyl ammonium chloride, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, and hexadecyl trimethyl ammonium chloride.
[0019] Furthermore, the amphoteric emulsifier is a polyol-type surfactant; preferably one or more of fatty acid ethylene glycol esters, monoglycerides, pentaerythritol fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters.
[0020] Furthermore, the defoaming agent is one or more of sunflower oil, polydimethylsiloxane, eicosanol, and docosanol.
[0021] Furthermore, the latex is one or more of natural latex, carboxylated styrene-butadiene latex, polyurethane latex, nitrile latex, and chloroprene latex.
[0022] Furthermore, the suspending agent is one or more of bentonite, kaolin, carbon black and talc.
[0023] Furthermore, the particle size of the suspending agent is 800-1800 mesh.
[0024] Furthermore, the fine sand particles are one or more of quartz sand, carborundum, corundum sand or basalt sand.
[0025] Furthermore, the particle size of the fine sand particles is 30-300 mesh; preferably, the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50-60%, the mass proportion of sand particles of 70-130 mesh is 20-30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10-30%.
[0026] Furthermore, the particle size of the odor-free temperature-controlling microcapsules is 1-5 μm.
[0027] Furthermore, the mass ratio of the composite shell material to the core material of the odor-free temperature-controlling microcapsule is 1:0.5-2.
[0028] Furthermore, the composite shell material of the odor-free temperature-controlling microcapsule includes silicon dioxide / nano-tourmaline / polydopamine, wherein the mass ratio of silicon dioxide to nano-tourmaline is 1-5:1, and the mass ratio of silicon dioxide to polydopamine is 1:0.1-0.5.
[0029] Furthermore, the normal alkane with a phase transition temperature of 40-60° C. is one or more of n-octadecane, n-eicosane, and n-docosane, preferably n-docosane.
[0030] Furthermore, the surface of the composite shell material is loaded with a metal chelate, wherein the metal is preferably copper.
[0031] Furthermore, the shell material surface is loaded with metal chelates and smoke suppressant compounds containing active α-H, the metal loading accounts for 0.1wt%-15wt% of the total mass of the odor-free temperature-controlling microcapsules; the smoke suppressant compound loading containing active α-H accounts for 0.1wt%-20wt% of the total mass of the odor-free temperature-controlling microcapsules.
[0032] Furthermore, the smoke suppressant compound containing active α-H is selected from one or more of aldehyde compounds having a carbon number greater than 9 or ketone compounds having a carbon number greater than 8.
[0033] Furthermore, the aldehyde compound having a carbon number greater than 9 is selected from one or more of o-methylcinnamaldehyde, p-methylcinnamaldehyde, anisaldehyde, 2-methylundecanal, 10-undecanal, ethyl vanillin, benzaldehyde, phenylacetaldehyde, p-hydroxybenzaldehyde, butylphenylmethylpropionaldehyde, neral, hydroxymethylpentylcyclohexene acetal, 3-(4-ethylphenyl)-2,2-dimethylpropionaldehyde, vanillin propanediol acetal, methylhexylcinnamaldehyde, methylpentylcinnamaldehyde, and diethylaminobenzaldehyde.
[0034] Furthermore, the ketone compound having a carbon number greater than 8 is selected from one or more of carvone, 3-hydroxy-2-butanone, 2,3-butanedione 3-pentene-2-one, and 6-methyl-3,5-heptadien-2-one.
[0035] Furthermore, the preparation method of the odor-free temperature-controlling microcapsule comprises the following steps:
[0036] S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the mixture under stirring, washing the mixture after the modification, and freeze-drying the mixture to obtain modified nano-tourmaline;
[0037] S2: heating the core material raw material until it is melted, then adding the solvent and the modified nano-tourmaline obtained in step S1, and stirring and mixing;
[0038] S3: adding a silicon dioxide precursor to the reaction system in step S2, stirring and mixing, and obtaining a Pickering emulsion;
[0039] S4: adjusting the pH value of the Pickering emulsion obtained in step S3 to 2-5, stirring and then aging, filtering, washing, and freeze-drying;
[0040] S5: adding the solid powder obtained in step S4 to a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying;
[0041] S6: adding the solid powder obtained in step S5, the smoke suppressant compound containing active α-H, and a strong base to an organic solvent, reacting under heating reflux conditions, cooling, filtering, washing, and freeze-drying;
[0042] S7: ultrasonically dispersing the solid powder obtained in step S6 in a metal ion salt-formamide solution, reacting under stirring, and after the reaction is completed, filtering, washing, and freeze-drying to obtain odor-free temperature-controlling microcapsules.
[0043] Furthermore, in step S1, the diameter of the nano-tourmaline is 10-100 nm.
[0044] Furthermore, in step S1, the surfactant is a cationic surfactant, preferably at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, and octadecyltrimethylammonium chloride, and more preferably cetyltrimethylammonium bromide.
[0045] Furthermore, in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.
[0046] Furthermore, in step S1, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (5-50):1.
[0047] Furthermore, in step S1, the stirring speed is 200-500 rpm; the modification temperature is 100-190° C., and the modification time is 2-5 hours.
[0048] Furthermore, in step S1, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0049] Furthermore, in step S2, the core material raw material is heated to a melting temperature of 40-60°C.
[0050] Furthermore, in step S2, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.
[0051] Furthermore, in step S2, the mass ratio of the core material raw material to the modified nano-tourmaline is (1-10):1, and the mass ratio of the solvent to the modified nano-tourmaline is (20-80):1.
[0052] Furthermore, in step S2, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.
[0053] Furthermore, in step S3, the silicon dioxide precursor is a silicate compound, preferably at least one of methyl silicate, ethyl orthosilicate, tetraethyl orthosilicate, and butyl orthosilicate, and more preferably ethyl orthosilicate.
[0054] Furthermore, in step S3, the mass ratio of the core material raw material to the silica precursor is (0.5-1.5):1.
[0055] Furthermore, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 40-7060° C., and the stirring time is 4-6 hours.
[0056] Furthermore, in step S4, the pH may be adjusted by dropwise addition of dilute acid, such as dropwise addition of dilute hydrochloric acid.
[0057] Furthermore, in step S4, the stirring speed is 400-600 rpm, the stirring temperature is 40-60° C., and the stirring time is 4-6 hours.
[0058] Furthermore, in step S4, the aging condition is: standing at 40-60°C for 12-30 hours. The freeze-drying condition is: vacuum drying at a temperature of -40--20°C for 4-8 hours.
[0059] Furthermore, in step S5, the buffer is one or more of phosphate buffer, carbonate buffer, and Tris buffer, preferably Tris buffer.
[0060] Furthermore, in step S5, the pH value of the buffer solution is preferably 8-10.
[0061] Furthermore, in step S5, the mass ratio of the buffer solution to the solid powder obtained in step S4 is (10-100):1.
[0062] Furthermore, in step S5, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.
[0063] Furthermore, in step S5, the stirring speed is 100-300 rpm, the stirring temperature is 20-40° C., and the stirring time is 12-24 hours.
[0064] Furthermore, in step S5, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0065] Furthermore, in step S6, the organic solvent is selected from one or more of methanol, butanediol, ethylene glycol, n-butanol, and anhydrous ethanol.
[0066] Furthermore, in step S6, the mass ratio of the solid powder obtained in step S5 to the smoke suppressant compound containing active α-H is 1:(10-40). The mass ratio of the solid powder obtained in step S5 to the organic solvent is 1:(20-80). The mass ratio of the solid powder obtained in step S5 to the strong base is 1:(0.5-2).
[0067] Furthermore, in step S6, the strong base is one of solid KOH and solid NaOH, preferably solid KOH.
[0068] Furthermore, in step S6, the reaction conditions of heating and reflux are: reaction temperature is 80-220° C., and reaction time is 5-10 hours.
[0069] Furthermore, in step S6, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0070] Further, in step S7, the metal ion salt is preferably a copper ion salt, and more preferably anhydrous copper sulfate.
[0071] Furthermore, in step S7, in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1.
[0072] Furthermore, in step S7, the mass ratio of the metal ion salt-formamide solution to the solid powder obtained in step S6 is (5-30):1.
[0073] Furthermore, in step S7, the stirring speed is 200-450 rpm, the reaction temperature is 100-190° C., and the reaction time is 2-5 hours.
[0074] Furthermore, in step S7, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0075] A second aspect of the present invention provides a method for preparing the above-mentioned odor-free temperature-controlled sand-containing fog seal layer, comprising the following steps:
[0076] P1: Preparation of composite emulsifier;
[0077] P2: Stir and mix water and part of the composite emulsifier prepared in step P1, adjust the pH value, and obtain a soap solution;
[0078] P3: After heating the asphalt and the soap solution obtained in step P2 respectively, shearing them to obtain emulsified asphalt;
[0079] P4: Add the remaining part of the composite emulsifier prepared in step P1 to the emulsified asphalt obtained in step P3, and stir to mix;
[0080] P5: Add defoaming agent to the reaction system of step P4 and stir to mix;
[0081] P6: Add a suspending agent to the reaction system of step P5 and stir to mix;
[0082] P7: Add the odor-free temperature-controlling microcapsules to the reaction system of step P6 and stir to mix;
[0083] P8: Add latex to the reaction system in step P7 and stir to mix;
[0084] P9: Add fine sand particles to the reaction system of step P8, stir and mix, and obtain an odor-free, temperature-controlled, sand-containing mist seal layer.
[0085] Furthermore, in step P1, the preparation of the composite emulsifier is to uniformly mix the cationic emulsifier and the amphoteric emulsifier.
[0086] Furthermore, in step P2, the water is preferably deionized. The mass ratio of the water to the composite emulsifier is: (5-20):1.
[0087] Furthermore, in step P2, the stirring speed is 100-600 rpm, the stirring temperature is 50-90° C., and the stirring time is 5-20 minutes.
[0088] Furthermore, in step P2, the pH can be adjusted by using an acetic acid aqueous solution, and the pH value is adjusted to 2-4.
[0089] Furthermore, in step P3, the heating temperature of the asphalt is 113-183°C. The heating temperature of the soap solution is 30-60°C.
[0090] Furthermore, in step P3, the shearing is preferably performed multiple times, and more preferably 3-5 times. The shearing rate is 3000-5000 rpm for each time, and the time for each time is 2-20 minutes.
[0091] Furthermore, the mass ratio of the composite emulsifier added in step P4 to the composite emulsifier added in step P2 is 1:2-5.
[0092] Furthermore, in step P4, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes.
[0093] Furthermore, in step P5, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes.
[0094] Furthermore, in step P6, the suspending agent is preferably added in multiple times, and more preferably added in 3-5 times.
[0095] Furthermore, in step P6, the stirring speed is 700-1600 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.
[0096] Furthermore, in step P7, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.
[0097] Furthermore, in step P8, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.
[0098] Furthermore, in step P9, the stirring speed is 100-600 rpm, the stirring temperature is 40-90° C., and the stirring time is 2-20 minutes.
[0099] Compared with the prior art, the present invention has the following advantages:
[0100] (1) The shell material of the temperature-controlling and odor-removing microcapsules of the present invention is a composite shell material comprising silica / nano-tourmaline / polydopamine. In the process of preparing the temperature-controlling and odor-removing microcapsules, the nano-tourmaline can replace the template agent for the synthesis of the microcapsules to maintain the stability of the microcapsule core material droplets. In addition, in the process of metal ion modification of the shell material, a large amount of metal ions can be adsorbed onto the surface of the microcapsules by means of the negative ion field released by the nano-tourmaline, effectively increasing the loading capacity of the transition metal ions in the microcapsule shell material. These metal ions can further react chemically with the sulfides released by the asphalt pavement at high temperature, effectively reducing The foul-smelling gases released by asphalt under the action of high temperature and sunlight can prevent asphalt roads from causing discomfort to the human body. Furthermore, during the service life of the road surface, when the temperature-controlling and odor-free microcapsules are heated, the nano-tourmaline contained in the shell material will release a negative ion field, further attracting the compounds released by the asphalt road surface under the action of high temperature to the vicinity of the temperature-controlling and odor-free microcapsules. While increasing the difficulty of these compounds to volatilize, the metal ions on the surface of the microcapsules and the smoke-suppressing compounds containing active α-H can react with more of the above-mentioned compounds, further inhibiting their volatilization, thereby effectively reducing the impact of the irritating gases released by the asphalt road surface on the human body.
[0101] (2) After the odor-free temperature-controlling sand-containing fog seal material of the present invention is spread on the road surface, the temperature of the road surface can be regulated in situ, which can not only effectively reduce the damage caused by high temperature to the road surface, but also extend the service life of the asphalt road surface. It can also prevent the asphalt road surface from releasing volatile organic compounds due to excessive temperature, thereby avoiding the generation of photochemical smog and haze.
[0102] (3) The odor-free temperature-controlling sand-containing mist seal material of the present invention has an excellent embedding effect on the road surface and can effectively extend the service life of the road surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0103] Figure 1 This is an electron microscope image of the odor-free temperature-controlling microcapsules obtained in Example 1. DETAILED DESCRIPTION
[0104] To further illustrate the technical solution of the present invention, the present invention will be clearly and detailed described below in conjunction with embodiments.
[0105] The present invention uses a scanning electron microscope to perform morphology testing, and the acceleration voltage used is 20 kV. Since the microcapsule wall material is not conductive, the sample needs to be treated with gold spraying before the test.
[0106] The smoke suppression effect of the odor-free temperature-controlling sand-containing mist sealing material of the present invention is tested by a VOC detector with an FID detector and a smoke detector with an H2S electrochemical sensor.
[0107] The base asphalt used in the following examples and comparative examples is Sinopec Donghai brand No. 70 Grade A asphalt.
[0108] Example 1
[0109] Preparation of temperature-controlled odor-free microcapsules:
[0110] S1: Add nano-tourmaline with a particle size of 90 nm, hexadecyltrimethylammonium bromide and formamide in a mass ratio of 4:1:40 into a first container, stir at 180°C and 400 rpm for 5 hours, then wash with ethanol for multiple times, and vacuum dry at -30°C for 5 hours to obtain modified nano-tourmaline for standby use;
[0111] S2: Add n-docosane to the second container, heat to melt at 50° C., then add formamide and the modified nano-tourmaline obtained in step S1, the mass ratio of n-docosane, the modified nano-tourmaline obtained in step S1 and formamide is 5:1:60, and stir at 50° C. and 400 rpm for 5 hours;
[0112] S3: adding tetraethyl orthosilicate to the reaction system of step S2, wherein the mass ratio of n-docosane to tetraethyl orthosilicate is 1:1, and continuing to stir at a speed of 400 rpm at 50° C. for 5 hours to obtain a Pickering emulsion;
[0113] S4: Use a peristaltic pump to slowly add 10 wt % dilute hydrochloric acid to the reaction system of step S3 until the pH of the reaction system is 4, continue stirring at 400 rpm at 50° C. for 5 hours, then stop stirring, keep the temperature unchanged and age for 24 hours, then filter and wash the solid powder in the reaction system, and vacuum dry it at -30° C. for 5 hours;
[0114] S5: adding the solid powder obtained in step S4 to a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the solid powder is 60:1, then adding dopamine hydrochloride to make the concentration of dopamine in the reaction system 5 mg / mL, stirring at 200 rpm for 12 hours at 25°C, then stopping stirring, filtering and washing the bottom solid powder, and vacuum drying at -30°C for 5 hours;
[0115] S6: Manually stir the smoke suppressant compounds of equal mass ratio: ethyl vanillin, methyl hexyl cinnamaldehyde, carvone, 6-methyl-3,5-heptadien-2-one, and then add the solid powder, anhydrous ethanol, and solid KOH obtained in step S5. The mass ratio of the solid powder, smoke suppressant compound, anhydrous ethanol, and KOH obtained in step S5 is 1:30:50:2. Then, react under heating reflux at 70°C for 6 hours, filter and wash the bottom solid powder, and vacuum dry at -30°C for 5 hours.
[0116] S7: Ultrasonic dispersion of the solid powder obtained in step S6 in a 50wt% anhydrous copper sulfate-formamide solution, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution being 1:20, stirring and reacting at 400 rpm and 140°C for 2 hours, filtering and washing the bottom solid powder after the reaction, and vacuum drying at -30°C for 5 hours to obtain a tasteless temperature-controlling microcapsule, the electron microscope image of which is shown in FIG. Figure 1 .
[0117] The preparation method of the odor-free temperature-controlling sand-containing fog sealing material is as follows:
[0118] P1: Add 2 parts by mass of palmitic acid amide propyl trimethyl ammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0119] P2: Add 50 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0120] P3: 45 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0121] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0122] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0123] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0124] P7: Add 35 parts by weight of odor-free temperature-control microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;
[0125] P8: Add 10 parts by mass of polyurethane latex and 15 parts by mass of natural latex to the system of step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0126] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50%, the mass proportion of sand particles of 70-130 mesh is 30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain the odor-free and temperature-controlled sand-containing fog sealing material.
[0127] Example 2
[0128] Except that the smoke suppression compound in step S6 is p-methylcinnamaldehyde, butylphenylmethylpropionaldehyde and 3-hydroxy-2-butanone in equal mass ratio, the rest is the same as that in Example 1.
[0129] Example 3
[0130] Except that in step S2, the mass ratio of n-docosane, the modified nano-tourmaline obtained in step S1 and formamide is 7:1:60, the rest is the same as that in embodiment 1.
[0131] Example 4
[0132] Except that in step S7, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:10, the rest is the same as that of Example 1.
[0133] Example 5
[0134] Except for step S6, the mass ratio of the solid powder, smoke suppression compound, anhydrous ethanol and KOH obtained in step S5 is 1:10:50:2, and the rest is the same as that of embodiment 1.
[0135] Example 6
[0136] Except that in step P7, the amount of the odor-free temperature-controlling microcapsules used is 10 parts by mass, the rest is the same as in Example 1.
[0137] Example 7
[0138] Except that in step P8, the latex added is 10 parts by mass of carboxylated styrene butadiene latex and 15 parts by mass of chloroprene latex, the rest is the same as in Example 1.
[0139] Example 8
[0140] Except that in step P8, the latex added is 5 parts by mass of carboxylated styrene butadiene latex and 7 parts by mass of chloroprene latex, the rest is the same as Example 1.
[0141] Comparative Example 1
[0142] Preparation of odor-free temperature-controlling microcapsules: Steps S1-S6 are the same as in Example 1, except that step S7 is omitted.
[0143] The preparation method of the odor-free temperature-controlling sand-containing fog sealing material is the same as that of Example 1.
[0144] Comparative Example 2
[0145] Preparation of temperature-controlled odor-free microcapsules:
[0146] S1: Add n-docosane to a container, heat to melt at 50°C, then add formamide and hexadecyltrimethylammonium bromide, the mass ratio of n-docosane, hexadecyltrimethylammonium bromide and formamide is 5:1:60, and stir at 50°C and 400 rpm for 5 hours;
[0147] S2: adding tetraethyl orthosilicate to the reaction system of step S1, wherein the mass ratio of n-docosane to tetraethyl orthosilicate is 1:1, and continuing to stir at 400 rpm at 50° C. for 5 hours to obtain a Pickering emulsion;
[0148] S3: Use a peristaltic pump to slowly add 10 wt % dilute hydrochloric acid to the reaction system of step S2 until the pH of the reaction system is 4, continue stirring at 400 rpm at 50° C. for 5 hours, then stop stirring, keep the temperature unchanged and age for 24 hours, then filter and wash the solid powder in the reaction system, and vacuum dry it at -30° C. for 5 hours;
[0149] S4: adding the solid powder obtained in step S3 to a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the solid powder is 60:1, and then adding dopamine hydrochloride to make the concentration of dopamine in the reaction system 5 mg / mL, stirring at a speed of 200 rpm at 25° C. for 12 hours, then stopping stirring, filtering and washing the bottom solid powder, and vacuum drying at a temperature of -30° C. for 5 hours;
[0150] S5: Manually stir the smoke suppressant compounds of equal mass ratio: ethyl vanillin, methyl hexyl cinnamaldehyde, carvone, 6-methyl-3,5-heptadien-2-one, and then add the solid powder, anhydrous ethanol, and solid KOH prepared in step S4, wherein the mass ratio of the solid powder, the smoke suppressant compound, anhydrous ethanol, and solid KOH prepared in step S4 is 1:30:50:2, and then react under heating reflux at 70°C for 6 hours, and then filter and wash the bottom solid powder, and vacuum dry it at -30°C for 5 hours;
[0151] S6: ultrasonically dispersing the solid powder obtained in step S5 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:20, stirring and reacting at 400 rpm and 140° C. for 2 hours, filtering and washing the bottom solid powder after the reaction is completed, and vacuum drying at a temperature of -30° C. for 5 hours to obtain odor-free temperature-controlling microcapsules;
[0152] The preparation method of the odor-free temperature-controlling sand-containing fog sealing material is the same as that of Example 1.
[0153] Comparative Example 3
[0154] Steps S1-S5 are the same as in Example 1;
[0155] S6: ultrasonically dispersing the solid powder obtained in step S5 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:20, stirring and reacting at 400 rpm and 140° C. for 2 hours, filtering and washing the bottom solid powder after the reaction is completed, and vacuum drying at a temperature of -30° C. for 5 hours to obtain odor-free temperature-controlling microcapsules;
[0156] The preparation method of the odor-free temperature-controlling sand-containing fog sealing material is the same as that of Example 1.
[0157] Comparative Example 4
[0158] P1: Add 2 parts by mass of palmitic acid amide propyl trimethyl ammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0159] P2: Add 50 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0160] P3: 45 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0161] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0162] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0163] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0164] P7: Add 10 parts by mass of polyurethane latex and 15 parts by mass of natural latex to the system of step P6, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0165] P8: Add 30 parts by mass of quartz sand to the system of step P7, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50%, the mass proportion of sand particles of 70-130 mesh is 30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain the sand-containing fog sealing material.
[0166] Comparative Example 5
[0167] When preparing the odor-free temperature-controlling microcapsules, steps S5-S7 are omitted, and steps S1-S4 are the same as in Example 1 to obtain a solid powder.
[0168] The preparation method of the sand-containing fog sealing material is as follows:
[0169] P1: Add 2 parts by mass of palmitic acid amide propyl trimethyl ammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0170] P2: Add 50 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0171] P3: 45 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0172] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0173] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0174] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0175] P7: Add 35 parts by mass of the solid powder obtained in step S4 to the system of step P6, and stir and mix at 500 rpm and 60° C. for 50 minutes;
[0176] P8: Add 10 parts by mass of polyurethane latex and 15 parts by mass of natural latex to the system of step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0177] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50%, the mass proportion of sand particles of 70-130 mesh is 30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain the odor-free and temperature-controlled sand-containing fog sealing material.
[0178] Comparative Example 6
[0179] The preparation method of the odor-free temperature-controlling microcapsules is the same as that of Example 1;
[0180] The preparation method of the odor-free temperature-controlling sand-containing fog sealing material is as follows:
[0181] P1: Add 2 parts by mass of palmitic acid amide propyl trimethyl ammonium chloride and 4 parts by mass of pentaerythritol fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0182] P2: Add 50 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0183] P3: 45 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0184] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0185] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0186] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0187] P7: Add 35 parts by weight of odor-free temperature-control microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;
[0188] P8: Add 30 parts by mass of quartz sand to the system of step P7, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50%, the mass proportion of sand particles of 70-130 mesh is 30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 20%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain the odor-free and temperature-controlled sand-containing fog sealing material.
[0189] Test Example 1
[0190] The paint wheel abrasion and the bonding strength with the base surface of the prepared odorless temperature-controlling sand-containing mist sealing material were tested, and the obtained data are shown in Table 1 below.
[0191] Table 1 Performance test of sand-containing fog seal
[0192] sample <![CDATA[Wet wheel wear value is / g·m -2 > 25℃ tensile strength / MPa Example 1 29.1 2.39 Example 2 29.2 2.39 Example 3 30.5 2.27 Example 4 30.0 2.32 Example 5 30.3 2.30 Example 6 30.9 2.26 Example 7 29.4 2.38 Example 8 31.5 2.21 Comparative Example 1 32.0 2.17 Comparative Example 2 32.9 2.11 Comparative Example 3 32.3 2.15 Comparative Example 4 33.5 2.08 Comparative Example 5 34.9 2.00 Comparative Example 6 74.3 1.21
[0193] Test Example 2
[0194] The gases released by asphalt pavement under the influence of high temperature are mainly volatile organic compounds and sulfides. In order to verify the smoke suppression ability of the odorless sand-containing fog sealing material of the present invention on asphalt materials, the samples prepared in the embodiments and comparative examples are sprinkled on the surface of the asphalt mixture test block. The size of the asphalt mixture test block is 10cm*10cm*3cm. The samples are further moved into a sealed container with a gas intake port and stored at a temperature of 80°C for 3 days. After the storage is completed, the gas in the sealed container is absorbed, and the VOCs and H2S contents in the gas are tested using a VOC detector and a smoke detector. The obtained data are shown in Table 2 below.
[0195] Table 2 Asphalt smoke test data
[0196] Test samples FID test value / ppm <![CDATA[H2S test value / ppm]]> Base asphalt 114.2 57.3 Example 1 40.1 14.4 Example 2 40.2 14.4 Example 3 43.2 15.6 Example 4 42.1 15.1 Example 5 42.5 15.3 Example 6 44.9 16.2 Example 7 40.2 14.5 Example 8 41.7 15.0 Comparative Example 1 64.3 23.2 Comparative Example 2 72.6 26.1 Comparative Example 3 69.0 25.1 Comparative Example 4 107.3 54.1 Comparative Example 5 80.2 28.9 Comparative Example 6 57.3 20.2
[0197] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A deodorizing temperature-controlling sand-containing mist seal, characterized in that: The components are as follows by mass: Asphalt: 35-70 parts; Water: 30-70 parts; Composite emulsifier: 2-8 parts; Defoaming agent: 0.5-3 parts; Latex: 5-40 parts; Suspension: 20-40 parts; Fine sand: 20-45 parts; Odor-free temperature-control microcapsules: 5-40 portions; The odor-free temperature-controlling microcapsule comprises a composite shell material and a core material, wherein the composite shell material comprises silicon dioxide / nano-tourmaline / polydopamine, the core material comprises normal alkanes with a phase transition temperature of 40-60°C, and the surface of the composite shell material is loaded with metal chelates and smoke-suppressing compounds containing active α-H.
2. The odor-free temperature-controlling sand-containing fog seal layer according to claim 1, characterized in that: The composite emulsifier includes a cationic emulsifier and an amphoteric emulsifier; the mass ratio of the cationic emulsifier to the amphoteric emulsifier is 1:0.5-2.5; Preferably, the cationic emulsifier includes one or more of amine salt surfactants having a carbon number greater than 8; preferably one or more of tetradecyl-dimethylpyridinium ammonium bromide, octadecylamidopropyl dimethyl dihydroxypropyl ammonium chloride, behenic acid amidopropyl dimethyl dihydroxypropyl ammonium chloride, hexadecylamidopropyl trimethyl ammonium chloride, dioctadecyl-methylbenzyl ammonium chloride, dodecyl dimethylbenzyl ammonium chloride, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, and hexadecyl trimethyl ammonium chloride; Preferably, the amphoteric emulsifier is a polyol-type surfactant; preferably one or more of fatty acid ethylene glycol esters, monoglycerides, pentaerythritol fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters.
3. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The defoaming agent is one or more of sunflower oil, polydimethylsiloxane, eicosanol, and docosanol; And / or, the latex is one or more of natural latex, carboxylated styrene butadiene latex, polyurethane latex, nitrile latex, and chloroprene latex; And / or, the suspending agent is one or more of bentonite, kaolin, carbon black, and talc; And / or, the fine sand particles are one or more of quartz sand, carborundum, corundum sand or basalt sand.
4. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The particle size of the odor-free temperature-controlling microcapsule is 1-5 μm.
5. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The mass ratio of the composite shell material to the core material of the odor-free temperature-controlling microcapsule is 1:0.5-2.
6. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The composite shell material of the odor-free temperature-controlling microcapsule comprises silicon dioxide / nano-tourmaline / polydopamine, wherein the mass ratio of silicon dioxide to nano-tourmaline is 1-5:1, and the mass ratio of silicon dioxide to polydopamine is 1:0.1-0.
5.
7. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The normal alkane with a phase transition temperature of 40-60° C. is one or more of n-octadecane, n-eicosane, and n-docosane, preferably n-docosane.
8. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The surface of the composite shell material is loaded with a metal chelate, wherein the metal is preferably copper; the surface of the shell material is loaded with a metal chelate and a smoke suppressant compound containing active α-H, the metal loading accounts for 0.1wt%-15wt% of the total mass of the odor-free temperature-controlling microcapsules; the loading amount of the smoke suppressant compound containing active α-H accounts for 0.1wt%-20wt% of the total mass of the odor-free temperature-controlling microcapsules.
9. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: The smoke suppressant compound containing active α-H is selected from one or more of aldehyde compounds having a carbon number greater than 9 or ketone compounds having a carbon number greater than 8; Preferably, the aldehyde compound having a carbon number greater than 9 is selected from one or more of o-methylcinnamaldehyde, p-methylcinnamaldehyde, anisaldehyde, 2-methylundecanal, 10-undecanal, ethyl vanillin, benzaldehyde, phenylacetaldehyde, p-hydroxybenzaldehyde, butylphenylmethylpropionaldehyde, neral, hydroxymethylpentylcyclohexene acetal, 3-(4-ethylphenyl)-2,2-dimethylpropionaldehyde, vanillin propanediol acetal, methylhexylcinnamaldehyde, methylpentylcinnamaldehyde, and diethylaminobenzaldehyde; Preferably, the ketone compound having a carbon number greater than 8 is selected from one or more of carvone, 3-hydroxy-2-butanone, 2,3-butanedione 3-pentene-2-one, and 6-methyl-3,5-heptadien-2-one.
10. The odor-free temperature-controlling sand-containing mist seal layer according to claim 1, characterized in that: The preparation method of the odor-free temperature-controlling microcapsule comprises the following steps: S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the mixture under stirring, washing the mixture after the modification, and freeze-drying the mixture to obtain modified nano-tourmaline; S2: heating the core material raw material until it is melted, then adding the solvent and the modified nano-tourmaline obtained in step S1, and stirring and mixing; S3: adding a silicon dioxide precursor to the reaction system in step S2, stirring and mixing, and obtaining a Pickering emulsion; S4: adjusting the pH value of the Pickering emulsion obtained in step S3 to 2-5, stirring and then aging, filtering, washing, and freeze-drying; S5: adding the solid powder obtained in step S4 to a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying; S6: adding the solid powder obtained in step S5, the smoke suppressant compound containing active α-H, and a strong base to an organic solvent, reacting under heating reflux conditions, cooling, filtering, washing, and freeze-drying; S7: ultrasonically dispersing the solid powder obtained in step S6 in a metal ion salt-formamide solution, reacting under stirring, and after the reaction is completed, filtering, washing, and freeze-drying to obtain odor-free temperature-controlling microcapsules.
11. The odor-free temperature-controlling sand-containing mist seal layer according to claim 1, characterized in that: In step S1, the surfactant is a cationic surfactant, preferably at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, and octadecyltrimethylammonium chloride; in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; And / or, in step S1, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (5-50):
1.
12. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: In step S2, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; And / or, in step S2, the mass ratio of the core material raw material to the modified nano-tourmaline is (1-10):1, and the mass ratio of the solvent to the modified nano-tourmaline is (20-80):
1.
13. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: In step S3, the silicon dioxide precursor is a silicate compound, preferably at least one of methyl silicate, ethyl orthosilicate, tetraethyl orthosilicate, and butyl orthosilicate, and more preferably ethyl orthosilicate; And / or, in step S3, the mass ratio of the core material raw material to the silica precursor is (0.5-1.5):
1.
14. The odor-free temperature-controlling sand-containing mist seal layer according to claim 1, characterized in that: In step S5, the buffer solution is one or more of a phosphate buffer solution, a carbonate buffer solution, and a tris(hydroxymethyl)aminomethane hydrochloride buffer solution, preferably a tris(hydroxymethyl)aminomethane hydrochloride buffer solution; the pH value of the buffer solution is preferably 8-10; And / or, in step S5, the mass ratio of the buffer solution to the solid powder obtained in step S4 is (10-100):
1.
15. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: In step S5, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.
16. The odor-free temperature-controlling sand-containing mist seal layer according to claim 1, characterized in that: In step S6, the organic solvent is selected from one or more of methanol, butanediol, ethylene glycol, n-butanol, and anhydrous ethanol; And / or, in step S6, the mass ratio of the solid powder obtained in step S5 to the smoke suppressant compound containing active α-H is 1:(10-40); the mass ratio of the solid powder obtained in step S5 to the organic solvent is 1:(20-80); the mass ratio of the solid powder obtained in step S5 to the strong base is 1:(0.5-2); And / or, in step S6, the reaction conditions of heating reflux are: reaction temperature is 80-220° C., and reaction time is 5-10 hours.
17. The odor-free temperature-controlling sand-containing mist seal according to claim 1, characterized in that: In step S7, the metal ion salt is preferably a copper ion salt, and more preferably anhydrous copper sulfate; in step S7, in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1; in step S7, the mass ratio of the metal ion salt-formamide solution to the solid powder obtained in step S6 is (5-30):
1.
18. A method for preparing the odor-free temperature-controlled sand-containing fog seal according to any one of claims 1 to 17, characterized in that: The steps include: P1: Preparation of composite emulsifier; P2: Stir and mix water and part of the composite emulsifier prepared in step P1, adjust the pH value, and obtain a soap solution; P3: After heating the asphalt and the soap solution obtained in step P2 respectively, shearing them to obtain emulsified asphalt; P4: Add the remaining part of the composite emulsifier prepared in step P1 to the emulsified asphalt obtained in step P3, and stir to mix; P5: Add defoaming agent to the reaction system of step P4 and stir to mix; P6: Add a suspending agent to the reaction system of step P5 and stir to mix; P7: Add the odor-free temperature-controlling microcapsules to the reaction system of step P6 and stir to mix; P8: Add latex to the reaction system in step P7 and stir to mix; P9: Add fine sand particles to the reaction system of step P8, stir and mix, and obtain an odor-free, temperature-controlled, sand-containing mist seal layer.
19. The preparation method according to claim 18, characterized in that: In step P2, the stirring speed is 100-600 rpm, the stirring temperature is 50-90° C., and the stirring time is 5-20 minutes; And / or, in step P4, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes; And / or, in step P5, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes; And / or, in step P6, the stirring speed is 700-1600 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P7, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P8, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P9, the stirring speed is 100-600 rpm, the stirring temperature is 40-90° C., and the stirring time is 2-20 minutes.
20. The preparation method according to claim 18, characterized in that: In step P2, the pH is adjusted using an aqueous solution of acetic acid to a pH value of 2-4.
21. The preparation method according to claim 18, characterized in that: The mass ratio of the composite emulsifier added in step P4 to the composite emulsifier added in step P2 is 1:2-5.